2011
DOI: 10.1007/s10865-011-9339-3
|View full text |Cite
|
Sign up to set email alerts
|

Core cognitions related to health anxiety in self-reported medical and non-medical samples

Abstract: The cognitive-behavioural model of health anxiety hypothesizes that the degree of health threat experienced by an individual is a function of the perceived: (1) likelihood of illness; (2) awfulness of illness; (3) difficulty coping with illness; and (4) inadequacy of medical services. While research has examined cognitions in health anxiety, it is not known whether these cognitions predict health anxiety in individuals who do or do not report medical conditions and whether these cognitions are uniquely related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 32 publications
8
70
1
2
Order By: Relevance
“…A total scale cut-off score of 18 is used to determine clinically significant health anxiety (Castellano et al, 2013;Rode, Salkovskis, Dowd, & Hanna, 2006). To examine both health anxiety, and catastrophic cognitions around future illness, this study included both the SHAI-total score (14-item main scale score, as used in Hadjistavropoulos et al, 2012) and the SHAI-NC supplementary subscale separately across analyses. Depression, Anxiety, Stress Scales-Short Form (DASS-21; Lovibond & Lovibond, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…A total scale cut-off score of 18 is used to determine clinically significant health anxiety (Castellano et al, 2013;Rode, Salkovskis, Dowd, & Hanna, 2006). To examine both health anxiety, and catastrophic cognitions around future illness, this study included both the SHAI-total score (14-item main scale score, as used in Hadjistavropoulos et al, 2012) and the SHAI-NC supplementary subscale separately across analyses. Depression, Anxiety, Stress Scales-Short Form (DASS-21; Lovibond & Lovibond, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…A number of cross sectional studies have demonstrated that these dysfunctional beliefs are specific to health anxiety and strongly associated and predictive of this disorder (e.g. Hadjistavropoulos et al, 2012;Fergus, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although the Internet has been used to administer measures of health anxiety and estimates of internal consistency have been reported [16][17][18][19][20][21], there is to our knowledge no previous study that has rigorously investigated the psychometric properties, including testretest reliability, of the Internet-administered HAI, IAS and WI using participants diagnosed with severe health anxiety. This is a major limitation as it cannot be taken for granted that reliability and validity estimates are the same when going from paper-and-pencil format to the Internet.…”
Section: Introductionmentioning
confidence: 99%